PERANCANGAN UI/UX APLIKASI NOTIFIKASI MASA STUDI MAHASISWA UIN AR-RANIRY BERBASIS ANDROID - Annisa Zahra; Sarini Vita Dewi (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
The Regulation of the Minister of Education and Culture (PERMENDIKBUD) No. 3 of 2020 states that the maximum study period for undergraduate students is seven years. This policy serves as an important guideline for universities to monitor and guide students to complete their studies on time. However, the current information system at UIN Ar-Raniry has not yet provided a dedicated notification feature that regularly reminds students about their study period. This research aims to design the User Interface (UI) and User Experience (UX) of an Android-based notification application, specifically created for students in their 5th semester and above at UIN Ar-Raniry. The study adopts the Design Thinking approach, which includes five key stages: Empathize, Define, Ideate, Prototype, and Test. Figma was used as the main tool for creating interactive prototypes. Data was collected through interviews and observations involving final-year students to explore their real needs and user behavior. Usability testing was conducted using the System Usability Scale (SUS) method, which resulted in an average score of 81.5, falling into the “excellent” category. This result highlights the importance of integrating strong UI/UX principles into educational applications. It also proves that intuitive design and a smooth user experience can significantly increase student awareness and discipline regarding their study limits. The application is expected to serve as a supportive solution for a more responsive and usercentered digital academic system.